2021
DOI: 10.1108/aeat-08-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation control using a bio-inspired nose for NACA 4 and 6 series airfoils

Abstract: Purpose This paper aims to achieve an optimum flow separation control over the airfoil using a passive flow control method by introducing a bio-inspired nose near the leading edge of the National Advisory Committee for Aeronautics (NACA) 4 and 6 series airfoil. In addition, to find the optimised leading edge nose design for NACA 4 and 6 series airfoils for flow separation control. Design/methodology/approach Different bio-inspired noses that are inspired by the cetacean species have been analysed for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Hence, it can be used in medium-speed transport aircrafts to increase the C l and the aerodynamic efficiency than the conventional high lift devices such as flap, slat, etc. (Raj Mohamed and Yadav, 2021) From the review, it has been inferred that the high lift devices are effective at high angle of attack to increase the coefficient of lift by increasing the camber. But they affect the low angle of attack aerodynamic performance by increasing the drag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it can be used in medium-speed transport aircrafts to increase the C l and the aerodynamic efficiency than the conventional high lift devices such as flap, slat, etc. (Raj Mohamed and Yadav, 2021) From the review, it has been inferred that the high lift devices are effective at high angle of attack to increase the coefficient of lift by increasing the camber. But they affect the low angle of attack aerodynamic performance by increasing the drag.…”
Section: Introductionmentioning
confidence: 99%
“…The bio-inspired nose designs, which are inspired by the cetacean species nose designs, were analyzed for the subsonic speed and found that the Dall’s Porpoise nose showed the better aerodynamic efficiency at all angles of attack with increase in C l (Raj Mohamed et al , 2019). The optimum bio-inspired (porpoise) nose enhances the aerodynamic efficiency for different NACA 4 and 6 series airfoils; hence, it can be made as a simple and fixed LE device which can be installed easily on the existing aircrafts (Raj Mohamed et al , 2021). The porpoise nose works well up to the critical Mach number and failed after that because of the shock wave formation.…”
Section: Introductionmentioning
confidence: 99%